(untitled) (Research, Society and Development, 2022)
Anxiety and depression are increasingly common mental disorders. Anxiety disorder is most often associated with physical and psychological symptoms, such as changes in behavior and mood, and unpleasant thoughts. The high rates of university students in the health area with depressive symptoms are also correlated with greater psychological susceptibility. The study was carried out through an integrative literature review. Using the Scientific Electronic Library Online (SCIELO), Google Scholar and Virtual Health Library (BVS-BIREME) databases. Courses in the health area have a higher prevalence of developing anxiety and depression. It is true that most university students resort to the use of psychotropic drugs, mainly anxiolytics and antidepressants, to alleviate the symptoms suffered by anxiety and depression. The general objective of this research is to review the literature available in free databases, on the factors, the prevalence and preference of use of which drugs, and the risks involved in their inappropriate use.